Honor thy father - Αρκάς (Flying starts, 1993)
Honor thy father... The little sparrow knows this biblical commandment all too well, since he spends most of his time violating it with all his might. But as he grows up his father is no longer a sufficient target for his scorn and contempt. So he flies to new horzons trying to get to know the world - which, however, proves uncooperative. Another perceptive volume on the meaning of life by the renowned Greek cartoonist Arkas in his series Flying Starts.